El trapito Feliz - Ross, Tony.; Dominguez, Catalina (Mexico Fondo de cultura economica, 1990)
Lucy is afraid of just about everything from spiders in the tub to shadows until she found a blanket for her security. Pablo on the other end of the book has a magic blanket to help him.
K-2.